«
  
»
Resolva as equações:
a)2(x+3)²-5(x+3)+2=0
b) (x-1).(x+3)=5
c) (3x+1)²+(x-2)²=25
d) x²-3√3+6=0
e) x+1 sobre x=3


RESOLVENDO

,
a) 2.(x+3)² -5.(x+3) +2= 0
2.(x²+2. x. 3+3²) -5x-15+2=0
2(x²+6x+9)-5x-13=0
2x²+12x+18-5x-13=0
2x²+12x-5x+18-13=0
2x²+7x+5=0
Por Bhascara:
 2x²+7x+5=0
Δ=b²-4. a. c
a=2, b=7 e c=5
Δ=7²-4.2.5
Δ=49-40
Δ=9
x=-b+-√Δ
  2. a
√9=3
x1=-7+3=   -4/4=-1
2.2
x2=-7-3= -10/4=-2,5
4
S=(-2,5 E -1)
b) (x-1).(x+3)=5
X²+3X-1X-3=5
x²+2x-3-5=0
 x²+2x-8=0
Por Bhascara:
  x²+2x-8=0
Δ=b²-4. a. c
a=1, b=2 e c=-8
Δ=2²-4.1.8
Δ=4+32
Δ=36
x=-b+-√Δ
  2. a
√36=6
x1=-2+6=   4/2=2
2.1
x2=-2-6= -8/2=-4
2
S=(-4 E 2)
C) (3x+1)²+(x-2)²=25
 (x-2)²=(x-2).(x-2)=x²-2x. 2+4
9X²+2.3X. 1+1²+(X-2)².=25
9X²+2.3X. 1+1²+(X²-2. X-2+4)=25
 9X²+6X+1+X²+4X+4-25=0
 10X²+10X -20=0( simplificando dividindo tudo por 10)
Por Bhascara:
  1X²+X -10=0 
Δ=b²-4. a. c
a=1, b=1 e c=-10
Δ=1²-4.1.10
Δ=1+40
Δ=√41
x=-b+-√Δ
  2. a
x1=-1+√41  
2.1
x2=-1-√41 
2
S=(x1=-1+√41e x2=-1 -√41
2           2
  
d) x²-3√3+6=0

X=+-\( \sqrt{-6+3. \sqrt{3} } \)
X=+-2,279507
e) 
\( \frac{x+1}{x} \)=3
x+1=3x
x-3x=-1
-2x=-1
2x=1
x=1/2
x=0,5

Na (b) (3x)²=9x² que será 10x²



O que achou desse conteúdo? Deixe seu comentário
TAREFAS SIMILARES: